2002
DOI: 10.1097/00007632-200206010-00019
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Standing and Sitting Postures on Trunk Muscle Activity in a Pain-Free Population

Abstract: The findings show that the lumbopelvic stabilizing musculature is active in maintaining optimally aligned, erect postures, and that these muscles are less active during the adoption of passive postures. The results of this study lend credence to the practice of postural retraining when facilitation of the lumbopelvic stabilizing musculature is indicated in the management of specific spinal pain conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
253
3
14

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 333 publications
(297 citation statements)
references
References 32 publications
13
253
3
14
Order By: Relevance
“…Among these are assuming particular postures 8 (O'Sullivan et al 2002), though this aspect is not considered a risk for the bone, muscular and articular apparatus by the Legislative Decree 81/08 (Decreto legislativo 81/08), but when these postures are incorrect (Colombini et al 1995) they may induce a sense of discomfort, fatigue and pain in a matter of a short term. A greater degeneration of the entire lumbar rachis, and particularly of the lower lumbar region, is also correlated to the handling of loads with frequent lifting, pushing and tractions, especially in absence of mechanical devices (Karahan et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Among these are assuming particular postures 8 (O'Sullivan et al 2002), though this aspect is not considered a risk for the bone, muscular and articular apparatus by the Legislative Decree 81/08 (Decreto legislativo 81/08), but when these postures are incorrect (Colombini et al 1995) they may induce a sense of discomfort, fatigue and pain in a matter of a short term. A greater degeneration of the entire lumbar rachis, and particularly of the lower lumbar region, is also correlated to the handling of loads with frequent lifting, pushing and tractions, especially in absence of mechanical devices (Karahan et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This was suggested to contribute to increased strain on the spinal tissues, potentially causing further damage and injury [6,70] and also to influence the trunk muscle activity role in spinal control and stability [2,5], which may perpetuate the spinal pain disorder and contribute to more disability [2,[4][5][6]. Establishing an accurate measure of a baseline posture that patients report to be painful may be invaluable with respect to evaluating the efficacy of postural re-education interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Although the link between posture and back pain is largely unknown, it has been speculated that end-of-range sitting and standing postures, that were shown to be associated with altered muscle activation patterns [1][2][3][4][5], may result in excessive loading of the passive spinal structures, eventual trauma and injury and could potentially pose a risk to the development of back pain [4,6]. Postural re-education is performed on the premise of optimizing spinal alignment to minimize stresses on the spinal structures and to improve trunk muscle efficiency in protecting the spine [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Maintaining a slumped sitting posture is a risk factor for work-related muscular disorders and is closely associated with the incidence of low back pain 11,14,15) . Dolan and Green 11) found that a prolonged slumped sitting posture resulted in impaired proprioception of "good posture" and repositioning sense.…”
Section: Discussionmentioning
confidence: 99%
“…Dolan and Green 11) found that a prolonged slumped sitting posture resulted in impaired proprioception of "good posture" and repositioning sense. In the slumped sitting posture, as compared to lumbopelvic sitting, muscular activation of the lumbopelvic region is reduced and body weight is supported by passive structures 15) .…”
Section: Discussionmentioning
confidence: 99%